1986
DOI: 10.1093/treephys/2.1-2-3.73
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between nutrient status, carbon assimilation and water use efficiency in Pinus radiata (D. Don) needles

Abstract: The productivity of Pinus radiata D. Don plantations can be increased on many soils by N and P fertilization. Foliar analyses are usually taken as a guide for nutrient management, but there is little information about the relationship of foliar nutrient status to foliar physiology. This paper provides such information from N and P fertilization experiments. The concentrations and contents of N and P in the needles of P. radiata change because of accumulation during needle growth, retranslocation during shoot g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
1
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(46 citation statements)
references
References 27 publications
2
42
1
1
Order By: Relevance
“…However, little is known about the effects of phosphorus deficiency on carbon assimilation in forest tree species (Ericsson and Ingestad, 1988). In Australia, P fertilization of Pinus radiata increased stand biomass and the maximal rate of photosynthesis (Sheriff et al, 1986). The same results were observed in Eucalyptus grandis seedlings (Kirschbaum et al, 1992).…”
mentioning
confidence: 78%
“…However, little is known about the effects of phosphorus deficiency on carbon assimilation in forest tree species (Ericsson and Ingestad, 1988). In Australia, P fertilization of Pinus radiata increased stand biomass and the maximal rate of photosynthesis (Sheriff et al, 1986). The same results were observed in Eucalyptus grandis seedlings (Kirschbaum et al, 1992).…”
mentioning
confidence: 78%
“…Increased growth in response to enhanced P availability was commonly reported for many tree species either in the field or under artificial growth conditions [9,52,55,57]. Chang [9] showed that increasing P supply from 0 to 50 kg P ha -1 increased basal diameter and height increment of two-month-old sweetgum seedlings by 24 and 22%, respectively.…”
Section: Introductionmentioning
confidence: 86%
“…Studies on interactions between light and phosphorus are still scarce, although phosphorus is a common limiting factor for tree growth in natural environments [52,57]. Increased growth in response to enhanced P availability was commonly reported for many tree species either in the field or under artificial growth conditions [9,52,55,57].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the effects of nutrient status on water-use efficiency, i.e, the quotient of biomass production to water use, remain scarce in tree species and practically all refer to leaf instantaneous wateruse efficiency (ratio CO^ assimilation rate/ transpiration rate, A/E). In most species, this ratio decreased when P (Sheriff, Nambiar & Fife, 1986;Guehl & Garbaye, 1990) or N (Sheriff et al, 1986;Reich, Walters & Tabone 1992) availability was authors (Stark, 1992 have found that A/E N concentration in Eucalyptus trees. The uniqueness among fo of water-use efficienc…”
Section: Introdl'ctionmentioning
confidence: 97%